Determining the origin of poor electronic conductivity and ultrafast ionic conductivity in Na3V2(PO4)2FO2 based on first principles and ab initio molecular dynamics methods. Issue 32 (3rd August 2022) - Guo, Yuhong; Xu, Li-Chun; Zhao, Wenyang; Guo, Chunli; Yang, Zhi; Liu, Ruiping; Shao, Jian-Li; Xue, Lin; Li, Xiuyan
Abstract : Maintaining layer-like features and regulating V atoms will be important directions to improve the performance of Na x V2 (PO4 )2 FO2 . Abstract : Sodium ion technology is increasingly investigated as a low-cost solution for grid storage applications. Among the reported cathode materials for sodium-ion batteries, Na3 V2 (PO4 )2 FO2 is considered as one of the most promising materials due to its high operation voltage and good cyclability. Here, the de-sodiumization process of Na3 V2 (PO4 )2 FO2 has been systematically examined using first-principles calculations to uncover the fundamental questions at the atomic level. Four stable intermediate products during the de-sodiumization process are firstly determined based on the convex hull, and three voltage platforms are then predicted. Except for two voltage platforms (3.37 V and 3.75 V) close to the experimental values, the platform up to 5.28 V exceeds the stability window (4.8 V) of a typical electrolyte, which was not observed experimentally. Excitingly, the change of volume is only 2% during the sodiumization process, which should be the reason for the good cycling stability of this material. Electronic structure analysis also reveals that the valence states of V ions will be changed from V 5+ to V 4+ during the sodiumization process, resulting in a weak Jahn–Teller distortion in VO5 F octahedra, and then making the lattice-constants asymmetrically change. More seriously, combined with a bandgap of 2.0 eV, the conduction band minimum mainly composed of V-t2g non-bonding orbitals has strong localized characteristics, which should be the intrinsic origin of poor electron transport properties for Na x V2 (PO4 )2 FO2 . Nonetheless, benefiting from the layer-like structure features with F-segmentation, this material has an ultrafast sodium ionic conductivity comparable to that of NASICON, with an activation energy of only 82 meV. Therefore, our results indicate that maintaining layer-like features and regulating V atoms will be important directions to improve the performance of Na x V2 (PO4 )2 FO2 .